FUNGSI JANGER SEBAGAI SARANA PEMBENTUKAN KARAKTER BAGI MASYARAKAT BANYUWANG: Janger, amusement, validating culture, education, and conformity of patterns of attitude, character building - Erwanto, Lambang (Fakultas Pedagogi dan Psikologi Universitas PGRI Adi Buana Surabaya, 2014)
Janger is one of Indonesian traditional arts that has an important role especially in a certain community or region. The functions of janger can fulfil people of Banyuwangi need of entertainment and education or information. Janger has amusement, validating culture, education, and conformity of patterns of attitude functions in which those are the means of information for the people. The story implied in janger can educate people about life and the other informations of social concern and also as means of character building.